Miniperc percutaneous nephrolithotomy versus retrograde intrarenal surgery in the treatment of juxta uretero-pelvic junction upper ureteric calculi: A prospective, randomized control study - T. P. Pradhyumna Koushik; Vivek Meyyappan; Nakul Baban Aher; Hariharasudhan Sekar; Gayathri Thiruvengadam; Sriram Krishnamoorthy (Urology Annals)
Introduction: Treatment of upper ureteric calculi has always remained a challenge for urologists. Treating the juxta-UPJ stones has been even more challenging. Difficulties in access, the possibility of up migration of stones, higher chances of leaving behind residual fragments, and the need for ancillary procedures like ESWL or relook URS have been a few inherent limitations in treating such stones. Offering PCNL for smaller stones was considered an overkill by many urologists. However, with the advent of miniaturized PCNL and improvisations in RIRS techniques, more and more of such stones are tackled with ease. Objective: To compare the safety and efficacy of mini-percutaneous nephrolithotomy (Miniperc PCNL) and retrograde intrarenal surgery (RIRS) in the management of juxta pelvi-ureteric junction (PUJ) calculi, located between 1 and 2 cm from PUJ. Materials and Methods: A prospective, randomized study was done on 100 patients with upper ureteric stones up to 2 cm in size and within 2 cm from PUJ. Patients with odd numbers were assigned Group A (Miniperc PCNL, n = 50) and even numbers were assigned to Group B (RIRS, n = 50). Results: Stone-free rates were 92% for Group A and 72% for Group B (P < 0.0174). Mean operative time was significantly shorter in Group A than Group B (53.2 min vs. 68.52 min, P < 0.001). Hospital stay was longer for Group A (47.42 h) compared to Group B (29.36 h, P < 0.001). Lasing time was more with RIRS than with PCNL (10.18 min vs. 3.24 min, P < 0.001). The complications were more in Group A than Group B, but not significant (P = 0.160). Postoperative pain and time to return to normal activities were significantly better in Group B RIRS (P < 0.001). Conclusions: Both Miniperc PCNL and RIRS are the effective treatments for upper ureteric stones. Miniperc PCNL has advantages in terms of shorter operative time, lesser lasing time, and better stone free rates. RIRS demonstrated reduced hospital stay, reduced postoperative pain, and quicker recovery. Miniperc PCNL showed a higher stone-free rate for treating upper ureteric stones up to 2 cm. RIRS is effective for treating stones up to 2 cm in upper ureter reducing the complications associated with Miniperc PCNL.